Analisis Rantai Pasok Produk Melon Hidroponik di PT Indigen Karya Unggul Kabupaten Sleman - Bayuardi Nugroho; Migie Handayani; Kustopo Budiraharjo (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2025)
Public consumption of high-quality horticultural products such as hydroponic melons has shown an increasing trend along with growing awareness of a healthy lifestyle, although overall fruit consumption in Indonesia remains relatively low. This commodity requires an efficient supply chain system to maintain product quality and continuity. This study aims to analyze the structure and performance of the hydroponic melon supply chain and evaluate its marketing efficiency at PT Indigen Karya Unggul, Sleman. The research employed a case study method using the Supply Chain Operation Reference (SCOR) approach. Data were collected through interviews, observations, and questionnaires involving 16 respondents, consisting of suppliers, producers, partner farmers, resellers, and consumers. This study addresses the research gap related to the limited in-depth analysis of high-quality horticultural supply chains such as hydroponic melons at the local company level. The novelty of this research lies in the integration of SCOR analysis with marketing efficiency evaluation through farmer’s share and marketing margin. The results show that supply chain performance based on the attributes of reliability, responsiveness, and flexibility falls under the superior category, while the cost attribute remains high at 61.65% of revenue. The supply chain efficiency is indicated by a farmer’s share of 100% in channel 1 and 56% in channel 2, as well as a marketing margin of IDR 0 in channel 1 and IDR 22,000 in channel 2, showing that channel 1 is proven to be more efficient. Overall, the company is still considered superior in terms of reliability and distribution speed, but improvements are needed in cost efficiency and asset management.